SUPERIORITY COMPLEX IN JANE AUSTEN’S EMMA - Mila, Agnes; Maru, Mister Gidion; Kumayas, Tirza A. (SoCul: International Journal of Research in Social Cultural Issues, 2023)
The aim of this research is to reveal Emma’s superiority complex in Jane Austen’s Emma. In conducting this research, the method used is qualitative. The main source of this research is the novel itself. The second sources are based on books, the internet, and articles to support the writers in conducting this study. In analyzing the data, the researchers use psychoanalysis theory. The result shows that the superiority complex is the one psychological disorder where the main character, Emma, feels superior compared to other characters. This attitude should not be allowed to develop because it can break other people’s character. There is nothing indication of psychological or social changed. Emma is lavishly praised by her father and governess, that prevent her from realizing her flaws and ill prepared her for life in the real world. Emma’s background is unclear, and she doesn’t learn anything about herself. Emma’s marriage is not a true match founded only on shared sentiments of love.